Expert perspectives on tuberculosis screening procedures for migrants - Marina Pinheiro; David N Moreira; Ana Aguiar; Raquel Duarte (Jornal Brasileiro de Pneumologia)
ABSTRACT Objective: To evaluate the perspectives of tuberculosis experts from different countries regarding national screening procedures. Methods: This was a qualitative descriptive study. Data were collected by using electronic, anonymized surveys with experts in tuberculosis in seven different countries within two World Health Organization regions (Europe and Africa). Thematic analysis was employed. Results: The survey results indicate that there are varied perceptions of and experiences with national guidelines on screening for and treatment of tuberculosis (especially in the population tested), the appropriate timing of screening, types of tests, best practices, barriers, and limitations of the screening. The participants highlighted the importance of integrating health care services into the community to achieve people-centered health care. The study also sheds light on the importance of involving trained nurses and social workers in the screening process and of networks to ensure continuity of care. Conclusions: The overall perceptions of the respondents underscore the importance of standardized screening guidelines. The ongoing collaboration between public health services, the private sector, and the community is essential to reduce tuberculosis transmission, as well as to provide substantial public health and economic benefits.